Experimental investigation on the flexural behavior of coarse aggregate reactive powder concrete (CA-RPC) bridge deck. (15th November 2022) - Liu, Zhao; Alsomiri, Mujahed; Li, Ming; Chen, Xiaohu; Meng, Jie
Highlights: High structural performance can be maintainedby including small-size coarse aggregate in the composition of RPC/UHPC. A cracking pattern featured by multiple micro- and macro-cracking prior to crack localization leads to enhanced ductility. Providing appropriate reinforcement ratio can guarantee sustained ductility after crack localization. Excessive deflections can be achieved before the failure of CA-RPC deck. Abstract: The high mechanical characteristics of reactive powder/ ultrahigh performance concrete have promoted its application in the bridge industry. Nonetheless, its employment in full structural components in bridges is hindered by the high cost and inconsistencies in the design guidelines. The addition of small-size coarse aggregate has been advocated by many researchers in pursuit of accomplishing a cost-effective and high-performance concrete. This paper introduces an innovative application of coarse aggregate reactive powder concrete (CA-RPC) and presents a comprehensive experimental investigation on the flexural behavior of a full-size prefabricated (CA-RPC) slab. The test results validated the sustained performance of RPC with the inclusion of coarse aggregate. The slab exhibited high capacity and excellent ductility, achieving an ultimate deflection to span ratio of about 1/8, accredited to the fibers and the appropriate reinforcement ratio. The resulting ductility was characterized by multiple micro-cracking at early stages, stable multiple macro-cracking prior to localization, slow localized crack growth and gradual concrete crushing. A detailed exploration of the cracking development and failure progression is provided, and a general evaluation of the performance of the slab under cyclic loading is also presented.